Use of 68Ga-PSMA-11 and 18F-FDG PET-CT Dual-Tracer to Differentiate Between Lymph Node Metastases and Ganglia - Shi, Yiping; Xu, Lian; Zhu, Yinjie; Wang, Yining; Chen, Ruohua; Liu, Jianjun (Frontiers in Oncology, 2021)
Purpose: Differentiating lymph node metastases (LNM) from peripheral ganglia by physiological prostate-specific membrane antigen (PSMA) uptake is challenging. Two tracers (68Ga-PSMA and 18F-fluorodeoxyglucose [FDG]) metabolic uptake patterns were evaluated by positron emission tomography-computed tomography (PET-CT), searching for differences that could tell ganglia from LNM. Methods: Dual 68Ga-PSMA and 18F-FDG PET-CT data of 138 prostate cancer patients acquired from June 2018 to December 2019 were retrospectively evaluated. Ganglia and LNM with PSMA uptake above local background were analysed by the location and PSMA-PET and FDG-PET maximum standardised uptake value (SUVmax). Results: PSMA-positive ganglia (n = 381) and LNM (n = 83) were identified in 138 and 58 patients, respectively. The LNM SUVmax of PSMA-PET (16.4 ± 14.8 vs 2.3 ± 0.7, P < 0.001) and FDG-PET (3.3 ± 3.2 vs 1.5 ± 0.5, P < 0.001) were higher than in ganglia. The probabilities of being an LNM in the low-potential (PSMA-PET SUVmax of <4.1 and FDG-PET SUVmax of <2.05), moderate-potential (PSMA-PET SUVmax of >4.1 and FDG-PET SUVmax of <2.05, or PSMA-PET SUVmax of <4.1 and FDG-PET SUVmax of >2.05), and high-potential (PSMA-PET SUVmax of >4.1 and FDG-PET SUVmax of >2.05) groups were 0.9% (3/334), 44.6% (37/83), and 91.5% (43/47), respectively (P < 0.001). The cervical and coeliac ganglia had higher PSMA and FDG uptake than the sacral ganglia (P < 0.001 for all). LNM PSMA and FDG uptake was similar in these three locations. Conclusion: The FDG-PET and PSMA-PET SUVmax, especially when combined, could well differentiate LNM from ganglia. The tracers uptake differed between cervical/coeliac and sacral ganglia, so the lesion location should be considered during image assessment.